Pancreatic lipomatosis - Schneeberger, Federico; Cardoso, Tabaré; Harretche, Martín; Wozniak, Angélica; Kvasina, Tomislav (Cirugía del Uruguay, 1986)
Description of two cases of pancreatic lipomatosis, secondary to chronic pancreatitis, one of them having been treated surgically. Pointed out its extremely rare occurence, obscure etiopathogeny and difficulties for the diagnosis. Stressed the importance of computerized axial tomography.